Enhancing Islamic Religious Education Outcomes Through Digital Learning Media: A Case Study at SMP IT Bina Insan Palu - Jannah, Fathul; Syahid, Ahmad; Arda (Al-Tawjih: Jurnal Pendidikan Islam, 2025)
The development of digital technology has brought significant changes to the learning process, including in Islamic Religious Education (PAI). Digital learning media are considered capable of enhancing learning effectiveness through more engaging visual and audio presentations as well as broader access to information. However, their implementation in schools does not always have an equal impact on improving student learning outcomes. This study aims to determine the influence of digital learning media on students’ learning outcomes in PAI at SMP IT Bina Insan Palu. This research employed a quantitative approach with a cross-sectional design. The sample consisted of 60 eighth-grade students selected using a saturated sampling technique. Data were collected through a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis included normality testing, t-test, and coefficient of determination using SPSS version 24. The findings show that the use of digital learning media has a significant effect on PAI learning outcomes, as indicated by t_calculated = 2.423 > t_table = 1.672 and a significance value of 0.019 < 0.05. The coefficient of determination (R²) of 0.092 suggests that digital media contribute 9.2% to learning outcomes, while the remaining 90.8% is influenced by other factors. Thus, it can be concluded that digital learning media play an important role in improving PAI learning outcomes, although their effectiveness is still influenced by supporting factors such as teacher strategies, student motivation, and the learning environment.